Training for export: A sociological study of Nurse exportation in Ghana - Nyameke, Emmanuel (University of Cape Coast, 2024)
This study explored the exportation of nurses as an alternative way of creating employment and generating revenue for the government by collecting data to inform policy on the export of nurses. In Ghana, data shows that 68,800 trained nurses between 2020 and 2022 have not been employed, as the country fails to absorb them into the health sector. Again, data continue to show that over 2000 nurses leave Ghana for other countries in search of job opportunities, quarterly every year. Using a sequential explanatory design, with data triangulated through questionnaires and in-depth interviews, comprising 483 nurses as respondents, 14 key informants and a video analysis of experiences of Ghanaian nurses in Barbados, the study found the consensus between nurses and stakeholders that exporting nurses was an avenue to reduce nurses’ unemployment, gain revenue, contribute to GDP. The quantitative findings underscored the need for policy development as a mechanism for effective nurses’ exportation with 89.4 percent of respondents scoring the need for policy, and86.1 percent of respondents buttressed the need to restructure the nursing colleges. The multinomial logistic regression revealed that number of children and willingness to be exported showed a statistical significance with a p-value of 0.033. The video data analysis revealed that exported nurses faced opposition, limited technological skills and cultural shocks in Barbados. The study therefore recommended that the government, through the Ministry of Health (MOH) and the Ministry of Employment and Labour Relations (MELR), consider formalising the export of nurses through bilateral agreements.
xvii, 271p;,ill